Estimation of longitudinal dispersion co-efficient: A review. Issue 1 (31st December 2016) - Tenebe, Imokhai Theophilus; Ogbiye, Adebanji Samuel; Omole, David Olugbenga; Emenike, PraiseGod Chidozie
Abstract: Accurate determination of longitudinal dispersion coefficient in rivers or streams is necessary for pollution control and management. This can be achieved through tracer studies and has proven to be a reliable method for measuring pollution spread. However, tracer studies practise which is expensive, time gulping and requiring large labour input have been substituted with empirical approaches thereby reducing the applicability of the dispersion coefficient models generated. This study reviews the various models derived as well as methods associated in the collection of tracer concentration data (measurement) existing in the literature. A sustainable approach to this study was identified and research needs were also listed.